2017
DOI: 10.18632/oncotarget.22027
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of quantitative HER2, HER3 and p95HER2 levels in HER2-positive advanced breast cancer patients treated with lapatinib following progression on trastuzumab

Abstract: Lapatinib is a HER1 and HER2 tyrosine kinase inhibitor (TKI) approved in second line treatment of advanced or metastatic breast cancer following progression on trastuzumab-containing therapy. Biomarkers for activity of lapatinib and other TKIs are lacking.Formalin-fixed, paraffin-embedded primary tumor samples were obtained from 189 HER2-positive patients treated with lapatinib plus capecitabine following progression on trastuzumab. The HERmark® Breast Cancer Assay was used to quantify HER2 protein expression.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…HER3 protein overexpression, for its part, has been shown to predict poor outcome in a group of HER2-positive breast cancer patients receiving adjuvant trastuzumab as a first-line therapy [ 25 , 29 ]. In contrast, a recently published study [ 44 ] postulates that HER3 is not an informative biomarker to predict trastuzumab sensitivity. Overall, it seems that the expression profile of any single HER protein, in addition to HER2, is insufficient to predict the trastuzumab response.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…HER3 protein overexpression, for its part, has been shown to predict poor outcome in a group of HER2-positive breast cancer patients receiving adjuvant trastuzumab as a first-line therapy [ 25 , 29 ]. In contrast, a recently published study [ 44 ] postulates that HER3 is not an informative biomarker to predict trastuzumab sensitivity. Overall, it seems that the expression profile of any single HER protein, in addition to HER2, is insufficient to predict the trastuzumab response.…”
Section: Discussionmentioning
confidence: 96%
“…Many studies did not find any demonstrable relationships between HER3 and patient survival [ 15 , 41 53 ]. Studies focusing on HER3 specifically in HER2 -amplified breast cancer [ 16 , 25 , 26 , 29 , 31 , 32 , 37 , 38 , 41 , 44 , 45 , 48 , 49 , 52 , 54 ] have not drawn conclusive results either. Interestingly, HER3 activation has been implicated as a molecular mechanism inducing inherent or acquired de novo resistance to anti-HER2 therapy [ 19 , 31 , 55 , 56 ].…”
Section: Introductionmentioning
confidence: 99%
“…The nonlinear U-shaped correlation between granular cytoplasmic staining of NPNT and survival is similar to that shown for various tumor markers in glioma [39] , prostate [40] , [41] , colorectal [42] , [43] , and pancreatic cancer [44] , [45] . In addition, a recent study reported a U-shaped correlation between HER2 protein expression and overall survival of breast cancer patients treated with the tyrosine kinase inhibitor lapatinib [46] . The explanation for this phenomenon is unclear in most cases.…”
Section: Discussionmentioning
confidence: 99%
“…tumorigenesis, and the expression of HER3 is upregulated in HER2-targeted therapy [24][25][26]. The increased HER3 expression promotes tumor immune tolerance, which can inhibit the PI3K signaling pathway [27].…”
Section: Agingmentioning
confidence: 99%
“…One of the problems in targeting HER3 in cancer is the lack of effective biomarkers to assess the HER3 activation in patients; this problem also hampers the patients screening [19,26]. Previous studies have suggested the use of HER3 chaperone kinases (such as HER2) as biomarkers, analysis of HER3 tumor levels using immunohistochemical assays, or using the expression of ligands that activate HER3 as biomarkers [29,30].…”
Section: Agingmentioning
confidence: 99%